Various clinical practice guidelines for sports-related concussion are of sufficient methodological quality by AGREE II: a systematic review. Issue 5 (2nd June 2020) - Dayton, Steven R; Baker, Hayden; Sheth, Ujash; Tjong, Vehniah K; Terry, Michael
Abstract : Importance: Clinical practice guidelines (CPGs) relating to concussion management are published by various healthcare specialties, including but not limited to orthopaedic surgery, family medicine, neurology and athletic trainers. A systematic analysis can help identify high quality CPGs for clinical use by sports medicine physicians. Objective: The purpose of this study is to systematically identify and appraise relevant CPGs related to sports-related concussion in adult patients. Evidence review: Predetermined selection criteria were used by two reviewers who independently identified published CPGs before 1 November 2018. CPGs were excluded if they focused only on paediatric patients or their scope was greater than concussion in the setting of sports. The remaining guidelines were analysed by five independent reviewers with different levels of training using the Appraisal of Guidelines for Research and Evaluation II tool. Guidelines were deficient if they earned scores less than 50%. The Spearman correlation coefficient was used to assess interobserver agreement between the evaluators. Scores were compared by publishing institution and healthcare discipline using Kruskal-Wallis tests. Findings: Seven CPGs met the inclusion criteria. Guidelines came from neurologists, athletic therapists/trainers and interdisciplinary sports medicine bodies. Interobserver agreement was strong and mean scores between surgical trainees (124.5) and board-certified surgeons (125.9) were not statistically different. Guideline quality was variable but not deficient (>50%), except regarding 'editorial independence'. No statistical difference was found between guidelines from different publishing institutions. Additionally, no statistical difference was found between guidelines published by different healthcare professionals. Conclusions and relevance: Overall, CPG quality was variable but not deficient, except for the domain of editorial independence. Bias due to poor editorial independence is a concern, particularly in CPGs published by non-physicians. Given the similarity in content and methodological quality, consideration should be given to condense evidence into a single CPG to be used by all healthcare professionals in the management of sports concussion. Level of evidence: 1, Systematic Review.